ChemInform Abstract: Temperature Induced Phase Transition of CaMn0.5Zr1.5(PO4)3 Phosphate. Issue 17 (April 2016) - Orlova, Maria; Perfler, Lukas; Tribus, Martina; Salnikov, Petr; Glorieux, Benoit; Orlova, Albina
Abstract: In view of a known structural phase transition at 800—875 °C and the by 10 times increased luminescence of Mn 2+ in the high‐temperature phase, low‐ (LT) and high‐temperature (HT) polymorphs of CaMn0.5 Zr1.5 (PO4 )3 are prepared by sol—gel reaction of Mn(O‐Ac)2, Ca(NO3 )2, ZrOCl2, and NH4 H2 PO4 in ethylene glycol followed by a final annealing (700 or 900 °C, 20 h, resp.).